A "Fourier Transformed Infrared" Compound Study of Lignin Recovered from a Formic Acid Process. (2016) - Rashid, Tazien; Kait, Chong Fai; Murugesan, Thanabalan
Abstract: Lignocellulosic biomass is emerging as a renewable source of feedstock for biorefinery and chemical industry. Lignin, one of the three components of lignocellulosic biomass (together with cellulose and hemicellulose) represents about 22% of the total mass of the Earth's biosphere. Formic acid was used to dissolve lignin at various reaction temperatures. Infrared spectroscopy was used to study the influence of temperature on the functional groups of treated lignin. Thermal treatment of lignin with formic acid causes a decrease of OH functional group of lignin and an increase of phenolic hydroxyl groups especially at elevated temperature. Results revealed that formic acid treatment resulted in oxidative cleavage of bonds in the lignin macromolecule, leading to formation of oligomers of lignin.